PENGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN PERTUMBUHAN PERUSAHAAN DAN PROFITABILITAS SEBAGAI VARIABEL MODERATING (Studi Empiris Perusahaan Properti Dan Real Estate Di BEI 2011-2015) - Jurnal Ilmiah Manajemen Universitas Putera Batam (Universitas Putera Batam, 2018)
This research aims to test the influence of the capital structure of the company with profitability and growth of the company as a variable moderation. The data used in this research is data skunder originating from the financial report of companies listed on the Indonesia stock exchange in 2011 - 2015. By using purposive sampling, this research got 30 sample company. Methods of analysis used in this study is a moderated regression analysis (MRA). The Result of research indicate that capital structure have an effect on positive to company value. Besides this research indicate that profitability can strengthen influence of capital structure to company value. Growth of company can strengthen influence of capital structure to company value.